Levofloxacin: Insights Into Antibiotic Resistance and Product Quality - Izadi, Ensieh; Afshan, Gull; Patel, Rahul P.; Rao, Venkatesan M.; Liew, Kai Bin; Meor Mohd Affandi, Meor Mohd Redzuan; Kifli, Nurolaini; Suleiman, Amal; Lee, Kah Seng; Sarker, Md. Moklesur R.; Zaidi, Syed Tabish; Ming, Long Chiau (Frontiers in Pharmacology, 2019)
Counterfeit and substandard medicines are recognized as one of serious threats to public health. The product quality of antibacterial medicine will compromise patients’ recovery and increase the chance of antibacterial resistance. The review aims to provide a summary of low quality levofloxacin issues and the risk factors as well as suggesting the aspects of product quality that need to be regulated strictly. Quality of the active ingredient, levofloxacin has an important role to contribute to successful therapy. The poor quality of raw material, directly and indirectly, causes treatment failure as the presence of insufficient dose, mislabeled content and poor dissolution characteristics can lead to lower bioavailability. Identifying and reporting these factors can potentially help in improving the quality of drug marketed in various developing countries and may also reduce the incidences of treatment failure. Dissolution test is used for testing the dissolution profiles and the rate of drug release from solid formulation such as oral formulations, thus providing information regarding the in vivo performance of a formulation and its bioequivalence. On the other hand, quality testing procedures are used for comparing the quality of products.